Geopolymer cellulose-based composite Black Carbon (BC)/Fe/Cu/polyvinyl alcohol for eco-friendly apron X-ray - Arif, Faradiba Tsani (Elsevier, 2023)
Composite geopolymer apron cellulose/black carbon (BC)/Fe–Cu/polyvinyl alcohol (PVA) has been successfully synthesized with variations in Fe–Cu (Cel/Bc I, Cel/Bc II, and Cel/Bc III) as shielding X-ray radiation by employing a simple approach characterized by Fourier Transform Infra-Red (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray mobile. The quantitative analysis of the FTIR spectrum using the Kramers-Kronig (K–K) relation was employed to analyze the optical properties, the refractive index (n), the extinction coefficient (k), real (ε1), and imaginary (ε2) of the dielectric function and the energy loss function. The analysis of XRD spectra demonstrated that the crystallite size decreases as the Fe concentration decreases in the composite’s apron and the best radiation shielding characteristics are shown in the Cel/Bc III sample with a small crystallite size of 12.72 nm. The quantitative analysis of X-ray mobile showed that the absorption properties of Cel/Bc III by the attenuation coefficient 0.441 cm